Empirical Study of Profitability Dynamics and Leverage in Interaction with Company Value - Ivayanti, Ni Nengah; Kurniawan, Putu Sukma; Herawati, Nyoman Trisna (LPPM Universitas Dhyana Pura, 2025)
This study aims to empirically examine profitability and leverage in relation to company value in the industrial sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This study applied secondary data and applied a quantitative approach. SPSS 26 is used as the data analysis tool. The results explain that profitability has a positive impact on corporate value with a test result of 0.010 < 0.05 and a t-value of 2.647 > t-table 1.987. These results are in line with signal theory, whereby high profits will have a positive impact on investor perception. Conversely, the test results for the interaction between leverage and company value did not show a significant effect. The test results were 0.760 > 0.05, and the t-value was -0.307 < t-table 1.987. Simultaneously, the variables in this study were able to influence company value with test results of 0.034 < 0.05. However, based on R2, it explains that the variables in this study can only explain 7.6% of the variation in company value, and the rest is caused by other factors.